TNFSF14 (LIGHT) in intestinal inflammation: balancing immune activation and resolution in IBD - Mousa, Rabia S.; Invernizzi, Pietro; Jones, Joanne L.; Mousa, Hani S. (Frontiers in Immunology, 2025)
Inflammatory Bowel Disease (IBD), encompassing Crohn’s disease and ulcerative colitis, is an umbrella term used to describe a group of autoimmune conditions characterized by chronic, relapsing inflammation of the gastrointestinal tract. The tumour necrosis factor superfamily member 14 (TNFSF14), also known as LIGHT, is a pleiotropic cytokine with diverse roles in immune regulation. Here, we review the multifaceted involvement of LIGHT in intestinal inflammation, particularly its dual capacity to both promote immune activation and facilitate inflammation resolution in the context of IBD. We explore the molecular mechanisms of LIGHT signalling through its receptors, Herpes Virus Entry Mediator (HVEM) and Lymphotoxin-β Receptor (LTβR), and how these distinct interactions dictate its pro-inflammatory or regulatory functions. Finally, we review the therapeutic potential of targeting this pathway, highlighting the results of recent clinical trials and exploring future strategies aimed at restoring immune homeostasis in patients with IBD.